Drifting Together : The Political Economy of Canada-US Integration - McDougall, John N. (Book collections on Project MUSE., 2006)
Drifting Together examines the effects of free trade on Canada-US relations beyond the dimensions of trade and investment flows. It traces the impact of the North American Free Trade Agreement (NAFTA) on Canada's cultural policies, communications regulations, cross-border regional interactions, social policy, defence and security policy, and foreign policies beyond the Canada-US relationship. This analysis sets the transformation of Canada-US relations against the backgrounds of both economic history and theories of economic and political integration. John McDougall argues that while the members of the NAFTA are highly unlikely ever to undertake the form of political integration adopted by the European Union, Canada is already engaged in a process of policy harmonization with the United States that amounts to political integration by stealth. Thus, the "integration question" is, for Canada, essentially a question of preserving its democracy